Marriage Registration Practice in Nepal - Kafle, Rameshwor (Baneshwor Campus Journal of Academia, 2023)
Marriage registration is a relatively more difficult and serious issue than other vital events registration. It was once viewed solely as a mechanism for recording life events and updating data on a regular basis, but in the modern world, it has evolved into a socio-economic and right-based approach. This study found, the practice of marriage registration in Nepal is yet unfamiliar. According to the study, women's age, literacy, media exposure, urban settlement, caste/ethnicity, occupation, wealth index and CEB appear to be the primary influencing elements in Nepal's marriage registration practice.